Analysis of Load Eccentricity in Cold-Formed Steel RHS Columns under Compression Considering Geometric Imperfections - Hodovanets Elvira; Kvocak Vincent (Selected Scientific Papers: Journal of Civil Engineering)
This research investigates the impact of hinged and fixed boundary conditions on the behavior of cold-formed steel rectangular hollow section (RHS) columns under eccentric compression. Theoretical analysis and numerical experiments were conducted to study the effects of geometric imperfections and eccentric loading on deformation and failure mechanisms. The findings highlight the significant influence of boundary conditions and geometric imperfections on the columns’ stability and load-bearing capacity. These results emphasize the need for careful consideration of these factors in the design and analysis of cold-formed steel structures.